On the issue of producing doubled haploids of table beet (Beta vulgaris L. var. conditiva Alef.) (a review) - A. M. Zaretsky; A. B. Kurina; D. V. Sokolova (Труды по прикладной ботанике, генетике и селекции, 2024)
Currently, hybrid table beet seeds make up a significant part of the seeds sold in the world due to their high synchrony, root uniformity, and the effect of heterosis. Heterosis breeding of table beet in Russia is developed insufficiently. One of the reasons is the lack of a well-studied homogeneous linear material. Another reason is a long and labor-consuming process of obtaining parent components for classical crossing due to a 2-year cycle of crop development, a pronounced self-incompatibility system, and inbreeding depression. In vitro production of doubled table beet haploids makes it possible to obtain homozygous material in a short time. It can be used in breeding programs as an alternative to traditional inbred lines. Therefore, introduction of the haploidization technology into the table beet breeding programs is of great importance. This article discusses various approaches to the production of doubled beet haploids and describes crucial achievements, major problems, and the ways to solve them. Methods for producing doubled haploids of table beet has not been studied profoundly enough, so they require additional in-depth research aimed at improving their efficiency and reproducibility.